Discrimination of Scots pine forests in the Iberian Central System (Pinus sylvestris var. iberica, Pinaceae) by means of pollen analysis. Phytosociological considerations - López Sáez, José Antonio; Sánchez-Mata, Daniel; Alba-Sánchez, Francisca; Abel Schaad, Daniel; Gavilán, Rosario G.; Pérez-Díaz, Sebastián (Lazaroa, 2013)
Fifty-eight modern pollen surface samples from different Scots pine forest communities (Pinus sylvestris var. iberica Svoboda) in the Iberian Central System (central Spain) were palynologically and statistically analyzed (using hierarchical cluster analysis and principal component analysis) to derive correlations between pollen assemblages and environmental gradients at the sampled points. Numerical classification and ordination were performed on pollen data to assess similarities among (central Iberian)-Scots pine forest phytosociological associations. The results show a strong relationship between altitude, temperature, rainfall, arboreal cover and variations in pollen taxa percentages. The statistic discrimination of some of these forest communities has allowed us to propose three new associations.